2009
DOI: 10.1021/jo9017638
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Dephosphorylation of Bis(2,4-dinitrophenyl) Phosphate in Mixed Micelles of Cationic Surfactants and Lauryl Hydroxamic Acid

Abstract: Mixed micelles of cetyltrimethylammonium bromide (CTABr) or dodecyltrimethylammonium bromide (DTABr) and the alpha-nucleophile, lauryl hydroxamic acid (LHA) accelerate dephosphorylation of bis(2,4-dinitrophenyl)phosphate (BDNPP) over the pH range 4-10. With a 0.1 mole fraction of LHA in DTABr or CTABr, dephosphorylation of BDNPP is approximately 10(4)-fold faster than its spontaneous hydrolysis, and monoanionic LHA(-) is the reactive species. The results are consistent with a mechanism involving concurrent nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…In our results, we found that BHA was slightly more hydrophobic than AHA and SHA, bound to cationic micelles hydrophobically as well as by electrostatic attraction, and has more efficient reaction with the bound substrate BNPP. It is considered that nucleophilicity is governed not only by the basicity but also by the strength of interaction between the nucleophile and the surfactant aggregate . The marked increase in nucleophilicity in micellar media was observed in the order BDMO > SHA > BHA > AHA > α‐benzoin oxime.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In our results, we found that BHA was slightly more hydrophobic than AHA and SHA, bound to cationic micelles hydrophobically as well as by electrostatic attraction, and has more efficient reaction with the bound substrate BNPP. It is considered that nucleophilicity is governed not only by the basicity but also by the strength of interaction between the nucleophile and the surfactant aggregate . The marked increase in nucleophilicity in micellar media was observed in the order BDMO > SHA > BHA > AHA > α‐benzoin oxime.…”
Section: Resultssupporting
confidence: 91%
“…Micellar rate effects have been quantitatively determined on the basis of pseudophase models that high local concentrations of nucleophiles are largely responsible for the rate acceleration in the interfacial micellar region . It was observed that cationic micelles accelerate the spontaneous hydrolysis of bis( p ‐nitrophenyl) phosphate (BNPP) up to 2 × 10 5 ‐fold and accelerate the reaction of hydroxamates and phosphate triesters . We herein examined micellar effects on the reactions of the less reactive phosphodiester with simple hydroxamates (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxamic acid structures in equilibrium Excellent contribution was made by Nome and co-workers [38] Hydroxamic acid structures in equilibrium Excellent contribution was made by Nome and co-workers [38] …”
Section: α-Nucleophilicty Of Hydroxamates In Watermentioning
confidence: 99%
“…Nome et al [38] through several techniques studied the products and the mechanism of the reaction between LHA and BDNPP. Nome et al [38] through several techniques studied the products and the mechanism of the reaction between LHA and BDNPP.…”
Section: Lossen Rearrangement In Micellesmentioning
confidence: 99%
“…The kinetic results reveal that hydroxamate attacks nucleophilically to the P=O center (Scheme ). Nome et al reported a detailed mechanism of a reaction of benzohydroxamate and laurylhydroxamate ion with bis(2,4‐dinitrophenyl) phosphate. NMR spectroscopy and ES‐MS study allow monitoring of the most important species with time for the reaction of BDNPP.…”
Section: Resultsmentioning
confidence: 99%